2022
DOI: 10.1002/cpt.2685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Prolongation of the Corrected QT Interval with Bedaquiline and Delamanid Coadministration to Predict the Cardiac Safety of Simplified Dosing Regimens

Abstract: Delamanid and bedaquiline are two drugs approved to treat drug-resistant tuberculosis, and each have been associated with corrected QT interval (QTc) prolongation. We aimed to investigate the relationships between the drugs' plasma concentrations and the prolongation of observed QT interval corrected using Fridericia's formula (QTcF) and to evaluate their combined effects on QTcF, using a model-based population approach. Furthermore, we predicted the safety profiles of once daily regimens. Data were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the present study, we found that LZD was usually combined with >3 drugs (such as bedaquiline, clofazimine and delamanid) according to the reporting system (see Table 4 for details). There is a large body of evidence that bedaquiline, delamanid and fluoroquinolones can cause QTp 16,19–21 . Therefore, the results obtained in this study may have been influenced by these drugs to some extent, exaggerating the role of LZD in the development QTp.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the present study, we found that LZD was usually combined with >3 drugs (such as bedaquiline, clofazimine and delamanid) according to the reporting system (see Table 4 for details). There is a large body of evidence that bedaquiline, delamanid and fluoroquinolones can cause QTp 16,19–21 . Therefore, the results obtained in this study may have been influenced by these drugs to some extent, exaggerating the role of LZD in the development QTp.…”
Section: Discussionmentioning
confidence: 68%
“…There is a large body of evidence that bedaquiline, delamanid and fluoroquinolones can cause QTp. 16,[19][20][21] Therefore, the results obtained in this study may have been influenced by these drugs to some extent, exaggerating the role of LZD in the development QTp.…”
Section: Discussionmentioning
confidence: 84%
“…Bedaquiline and its primary metabolite M2 exposures at the current standard dosing regimen (400 mg once daily for 14 days followed by 200 mg three times weekly) have the potential for safety concerns related to QTc interval prolongation and hepatic adverse events [ 10 12 ]. Alternative once-daily dosing (200 mg once daily for 8 weeks followed by 100 mg once daily) of bedaquiline is of interest to increase patient adherence to obtain optimal efficacy [ 12 ]. Pretomanid has overall acceptable clinical safety profiles; however, pretomanid combined with bedaquiline and linezolid can have additive effects, leading to an increased potential of certain adverse effects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative bedaquiline dosing, 200 mg QD for 9 weeks followed by 100 mg QD, has been proposed. Prior analyses predicted comparable safety concerns associated with alternative bedaquiline dosing and approved dosing 35 . Our simulations suggested a minor difference in Mtb clearance following bedaquiline QD dosing compared to the approved dosing.…”
Section: Discussionmentioning
confidence: 69%
“…Prior analyses predicted comparable safety concerns associated with alternative bedaquiline dosing and approved dosing. 35 Our simulations suggested a minor difference in Mtb clearance following bedaquiline QD dosing compared to the approved dosing. Linezolid has been a key drug in more than five drug combination regimens and was widely used for the treatment of MDR-TB before the availability of bedaquiline and pretomanid.…”
Section: Simulations Of Anti-mtb Activity Following Bpal At Approved ...mentioning
confidence: 74%